Pro dan Kontra Implementasi Program Sertifikasi Guru dalam Peningkatan Mutu Pendidikan di Nanggroe Aceh Darussalam - Hafni, Nur (Jurnal Demokrasi, 2011)
Regulation No. 14 Year 2005 regarding Teacher Certification is one of the government's efforts to improve the professionalism of teachers. In reality, the implementation of teacher certification program faced many obstacles. The finding of this study indicated that the teacher certification program has shifted the value of professionalism to the increased prosperity, so that teacher certification has not influence on quality improvement. The regulation of Teacher Certification still thick with political overtones, and did not reflect the good political will to increase teacher professionalism. Â  Kata kunci: implementasi, sertifikasi guru, profesionalitas guru, peningkatan mutu pendidikan, peningkatan kesejahteraan